The Practice of Rain Water Harvesting as A Flash Flood Mitigation Measure in Ken Rimba Shah Alam, Selangor - Asmawi, M. Zainora (2019)
Malaysia is one of the countries facing frequent flash flood problems in the urban area due to city expansion and rapid development, poor drainage system and the effects of natural system. There is a dire need for all relevant agencies to adopt new strategies to reduce the frequencies of flash floods that are plaguing the fully developed river basins, namely the Klang River Basin. Therefore, the objective of the study is to assess the practice of Rain Water Harvesting (RWH) in mitigating the occurrence of the flash flood in Ken Rimba Shah Alam, Selangor. A total of 194 Ken Rimba residences have been selected as the respondents to obtain the primary data on the awareness and acceptance towards RWH. Their perception towards the potential of RWH as a flash flood mitigation measure in the study area are also essential. It is important that the study appreciate the perception of the community as they are living at flood-prone areas and likely very much be affected during the flash flood especially during the heavy rain in monsoon season. The results of questionnaire survey indicate that, there is not enough awareness amongst the residents of RWH benefits as the mitigation measures of flash flood. Thus, the study suggests for promoting RWH through mass media to the public to achieve long-term sustainability and resiliency that can be a flash flood mitigation measure especially in the planned residential area. All recommendations have involved many parties to promote the rainwater harvesting to safeguarding the urban areas in nurturing communities that are simultaneously coping with climate change in this rapid urbanisation area.